CORAK DAN METODOLOGI TAFSIR ALQURAN AL-MADJID AN-NUR KARYA HASBI ASH-SHIDDIEQY - M. Abdurrahman Wahid (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
The interpretation of the Qur'an has begun since the Holy Qur'an was delivered by the prophet Muhammad SAW to his people, this is a historical reality that cannot be denied by anyone including western and eastern historians, both Muslim and non-Muslim. Then the interpretation of the Qur'an in Indonesia is an effort made to explain the contents of the Qur'an to the Indonesian people through the language used by the nation. In the study of the interpretation of the Qur'an in Indonesia's early period, the interpretation of the Qur'an in Indonesian was marked by the emergence of several translations and interpretations of juz uz amma. The interpretations that existed at that time were still partial and not yet a complete interpretation. Until later in the late 60's, Hamka began writing an interpretation which was later called the interpretation of al-Azhar. Besides that Hasbi ash-Shiddieqy also compiled an interpretation entitled al-Qur'an al-Madjid in several volumes and then gathered it into an-Nur's interpretation and refined it into al-Bayan's interpretation. This paper will try to discuss the interpretation of an-Nur by Hasbi ash-Shiddieqy. The method used in the interpretation is the method of tahlili (analytical) and muqaran (comparative) while the interpretation style is the interpretation of al-Adabi> wa al-Ijtima>'iy. An-Nur's interpretation is one of the major influential works in Indonesia, it is evident that this interpretation book is a reference for PTAIN in Indonesia, both in the Faculty of Islamic Education and in the Faculty of Sharia